1998
DOI: 10.1098/rspb.1998.0316
|View full text |Cite
|
Sign up to set email alerts
|

Blue tits are ultraviolet tits

Abstract: The blue tit (Parus caeruleus) has been classi¢ed as sexually monochromatic. This classi¢cation is based on human colour perception yet, unlike humans, most birds have four spectrally distinct classes of cone and are visually sensitive to wavelengths in the near-ultraviolet (300^400 nm). Re£ectance spectrophotometry reveals that blue tit plumage shows considerable re£ection of UV light. For example, the blue crest shows peak re£ectance at wavelengths around 352 nm. Furthermore, the blue tit is sexually dichrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
225
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(233 citation statements)
references
References 26 publications
7
225
0
1
Order By: Relevance
“…Although evidence of hidden UV colour patterns was very rare, we did find that cryptic dimorphism, as first discovered in blue tits (Hunt et al 1998;Andersson et al 1998), might be substantially more common among birds. Based on our observations, we could not perceive coloration differences in feather patches whose associated spectra differed in reflectance by as much as 10% across the human-visible portion of the spectrum.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Although evidence of hidden UV colour patterns was very rare, we did find that cryptic dimorphism, as first discovered in blue tits (Hunt et al 1998;Andersson et al 1998), might be substantially more common among birds. Based on our observations, we could not perceive coloration differences in feather patches whose associated spectra differed in reflectance by as much as 10% across the human-visible portion of the spectrum.…”
Section: Discussionmentioning
confidence: 85%
“…Second, our definition would classify as monomorphic those patches that differed by less than 5% at the peak sensitivity of the UV cone, even though research has shown that such small UV differences (less than 5%) can influence behaviour (e.g. Bennett et al 1997;Andersson et al 1998;Hunt et al 1998;Siitari et al 2002). The existence of cryptic dimorphism produced by sexual differences in structural colours that humans are incapable of seeing, suggests that there is a class of sexually selected traits of which human observers have been unaware.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to foraging, blue tits are dimorphic in the UV and seem to use these cues in mate choice (Andersson et al 1998;Hunt et al 1998). Furthermore, some of the light environments likely to be present in a blue tit's habitatö`woodland shade' (Endler 1993b) in particularömay be quite rich in short wavelength light.…”
Section: Discussionmentioning
confidence: 99%
“…focused on three hypotheses regarding the functional signi¢cance of avian UV vision: (i) mate choice, (ii) foraging, and (iii) navigation. To date, behavioural studies have provided evidence that UV cues play an important role in conspeci¢c signalling in several bird species (Maier 1993;Bennett et al 1996Bennett et al , 1997Andersson & Amundsen 1997;Hunt et al 1997Hunt et al , 1998Andersson et al 1998). Here, we focus on the hypothesis that UV vision enhances foraging.…”
Section: Introductionmentioning
confidence: 99%